Fecal microbiota transplantation validates the importance of gut microbiota in an ApoE−/− mouse model of chronic apical periodontitis-induced atherosclerosis - Guowu Gan; Ren Zhang; Yu Zeng; Beibei Lu; Yufang Luo; Shuai Chen; Huaxiang Lei; Zhiyu Cai; Xiaojing Huang (BMC, 2024)
Abstract Background Chronic apical periodontitis (CAP) has been linked to the development of atherosclerosis, although the underlying mechanisms remain unclear. This study aimed to investigate the role of gut microbiota disruption in CAP-induced atherosclerosis development, focusing on trimethylamine N-oxide (TMAO)-related metabolites. Methods The study utilized fecal microbiota transplantation (FMT) to transfer gut microbiota from mice with CAP to healthy mice. Atherosclerosis development was assessed by analyzing lesions in the aortic arch and aortic root. Serum lipid and inflammatory factor levels were measured. Composition and diversity of gut microbiota were analyzed using targeted metabolomics, with a focus on the ratio of Firmicutes to Bacteroidetes. The expression of hepatic flavin-containing monooxygenase 3 (FMO3) and serum TMAO levels were also evaluated. Results Mice receiving gut microbiota from CAP mice showed increased atherosclerotic lesions compared to controls, without significant differences in serum lipid or inflammatory factor levels. Alterations in gut microbiota composition were observed, characterized by an increase in the Firmicutes to Bacteroidetes ratio. Peptostreptococcaceae abundance positively correlated with atherosclerosis severity, while Odoribacteraceae showed a negative correlation. No significant differences were found in hepatic FMO3 expression or serum TMAO levels. Conclusions The study confirms the role of gut microbiota disruption in CAP-mediated atherosclerosis development, independent of serum lipid or TMAO levels. Alterations in gut microbiota composition, particularly increased Firmicutes to Bacteroidetes ratio and specific bacterial families, were associated with atherosclerosis severity. These findings highlight the intricate interplay between gut microbiota and cardiovascular health in the context of CAP.